HUBUNGAN ANTARA LINGKUNGAN SEKOLAH DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 10 KOTA BATAM TAHUN 2017 - Azura, Melur; Sihombing, Sarmauli Franshisca Siho Franshisca (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2017)
Â Most of student doesnâ€™t like to study mathematic. This course is still assumed as the difficult lesson to be learned by student from elementary, junior high school, senior high school even varsity. Thus, for the student who belief incapable doing the math task, they are loath to learn mathematic. It is proven from the interview result with respondent and people outside. It is possible bring this lesson on student to receive low score. This research aims to examine the relationship between school environment and math performance on student grade VIII in SMPN 10 Batam 2017. This research is using analytic study design by employing cross-sectional approach. The population involved the student of SMPN 10 Batam with 83 respondents. The result shows that there is no correlation between school environment and math performance on student grade VIII in SMPN 10 Batam 2017. The data analyzing technique is chi square test with p - value = 0,185 > 0,05. In suggestion, for the educational institution which is the place for teaching and learning process, it is expected to provide both infrastructures and environmental of school well to support safe and confinement learning process for the student.Â